Verificação da capacidade resistente de uma travessa de ponte através do método de bielas e tirantes - SOUSA, Lukas Ribeiro Moura de (2023)
Bridge pier caps beam are structural elements of reinforced concrete bridges that are responsible for receiving the load from the main girders and transversely connecting the piers. This structural system is part of the bridge's mesostructure, which aims to transmit the bridge's forces to the foundation. The load-carrying capacity of the bridge pier cap is important for the performance and safety of the bridge. The technical requirements of the design must comply with the current normative recommendations, and the technical analysis of the projects is essential to ensure the quality of the construction. The verification methodology should be consistent with the geometry, constraints, and structural behavior of the element. For structures subjected to unusual boundary conditions, the strut-and-tie method proves to be an option, given its comprehensiveness in cases of geometric discontinuity and loadings. The method works with an idealized truss within the structural element, representing the flow of discretized compression forces (struts) and tension forces (ties). This allows for the verification of concrete strength in critical regions, as well as the determination and arrangement of reinforcements. Therefore, the present work aims to verify the design of an unconventional bridge pier cap geometry’s using the strut-and-tie method, with the assistance of STRAP software for the elastic analysis of stresses. With it, it was possible to outline the truss model and verify it according to the normative recommendations of ABNT NBR 6118 (2014). Finally, the goal is to contribute to diversifying the potential applications of the strut-and-tie method for possible situations that structural engineers may encounter in their professional routine.